Preparation and electromagnetic shielding effectiveness of cobalt ferrite nanoparticles/carbon nanotubes composites. (18th March 2019) - Wang, Min; Zhang, Yanlin; Dong, Chengjun; Chen, Gang; Guan, Hongtao
Here, the cobalt ferrite/carbon nanotubes nanocomposites were directly synthesized by a facile hydrothermal method at 200°C using benzyl alcohol as the solvent. The crystal and morphological structures as well as electromagnetic shielding performance at Ku band (12–18 GHz) were thoroughly investigated. Cobalt ferrite nanoparticles with a diameter around 6–10 nm were anchored on the surface of carbon nanotubes with some aggregation. It is found that the as-prepared nanocomposites exhibit excellent electromagnetic shielding performance with values 22–25 dB in the Ku frequency range with a thickness of 2 mm. The small cobalt ferrite nanoparticles offer a large number of polarization and magnetization active sites to improve the electromagnetic performance by the incorporation of carbon nanotubes.